(untitled) (Education in the 21st Century, 2023)
The article presents the main approaches to the organization and prevention of myopia in children in the family. It is known that visual impairment, including myopia, is often observed in childhood, when a child in the family does not follow the rules, regulations, and requirements set for the protection of vision and visual work during games, drawing, viewing pictures, drawings, computer activities, etc. The preservation of good vision mainly depends on how parents are informed about the prevention of myopia in children. This determines the necessity of developing of approaches for prevention of myopia in children in the family and for provision the informational assistance to parents in these matters. This problem is complicated by the fact, that many parents do not pay needed attention to the conditions of conducting the child’s visual work, and often do not have the necessary information about the rules and standards of visual work and rest of the child’s eyes. Therefore, the study of many aspects of this problem and the development of approaches for providing the informational assistance to parents on the prevention of myopia in children in the family will be the basis for a successful solution to this problem and maintaining good vision in children. Thus, this article is based on the study of special literature and the experience of some families in observing the rules, norms, basic requirements and conditions of visual work and rest of the eyes of the child in various types of activities, and presents a number of questions and defines the main directions the family should pay great attention to for developing good vision in the child and for preventing myopia.